Socioeconomic inequities of malaria prevalence in under-five children in Ghana between 2016 and 2019 - Edusei, Marian (Unknown, 2025)
Background Globally, malaria is a preventable and treatable disease that still accounts for thousands of deaths annually, putting approximately 3.3 billion people at risk. Children under five are the most affected, with Sub-Saharan Africa bearing the highest burden. In Ghana, malaria causes nearly 20,000 child deaths each year, a quarter of which are in children under five. Although the association and socioeconomic inequalities related to malaria prevalence have been studied, there is limited evidence on socioeconomic status (SES)-related inequality in malaria prevalence among Ghanaian children under five. Understanding these inequalities is crucial for Ghana to advance towards its sustainable developmental goals (SDG) 10, which focuses on reducing inequalities, and SDG 3, which promotes health and well-being. Methods The study adopts a literature review structured into theoretical, methodological, and empirical sections. It discusses the economic burden of malaria and defines theoretical frameworks for SES-related inequalities, using the commission of social determinants of health (CSDH) framework as the conceptual foundation. Methodologies for measuring SES-related inequalities and methods for decomposition analysis are reviewed. Using the period between 2020-2024, the empirical review focused on socio-economic related inequalities in malaria. The 2016 and 2019 Ghana malaria indicator survey datasets were analysed using Stata 15. The outcome variable was malaria prevalence in under-five children, explanatory variables included socio-economic status (household wealth), age of child, mother's education, place of stay, region and a few others. Our study applied the concentration indices and curves to assess socioeconomic inequalities in malaria prevalence among under-five children and decomposing the concentration index to identify contributing socioeconomic factors. Results The 2019 concentration index was significantly negative (CI= -0.224; SE=0.059), indicating a higher prevalence of malaria in children from lower socioeconomic backgrounds. While the 2016 index was not statistically significant, it was still negative, suggesting a pro-poor bias in malaria prevalence (CI= -0.052; SE= 0.053). The decomposition analysis found that wealth index, region, and ethnicity were significant contributors to the observed inequalities, accounting for 59.28%, 23.51%, and 4.15% of them, respectively, in 2019. Conclusion There are pro-poor inequalities in malaria prevalence among under-five children in Ghana, with a higher burden on those from lower SES backgrounds. Malaria intervention programs should be tailored to target these vulnerable populations and regions that are disproportionately affected by the disease to effectively combat malaria and advance toward meeting the SDGs related to health and inequality.